2023
DOI: 10.1002/adhm.202300321
|View full text |Cite
|
Sign up to set email alerts
|

Controllable‐Swelling Microneedle–Assisted Ultrasensitive Paper Sensing Platforms for Personal Health Monitoring

Abstract: Microneedle (MN) patches, which allow the extraction of skin interstitial fluid (ISF) without a pain sensation, are powerful tools for minimally invasive biofluid sampling. Herein, an MN‐assisted paper‐based sensing platform that enables rapid and painless biofluid analysis with ultrasensitive molecular recognition capacity is developed. First, a controllable‐swelling MN patch is constructed through the engineering of a poly(ethylene glycol) diacrylate/methacrylated hyaluronic acid hydrogel; it combines rapid,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…Thus, we tested the utilized materials for cytotoxicity, as well as for biocompatibility to overgrowing cells. According to the ISO 10993 standard, ≥30% reduction in cell viability after exposure to a device is considered cytotoxic. , First, we ran an indirect cytotoxicity test using the individual materials and combinations of materials. Specifically, the materials were incubated for 24 h in the culture medium ( t = 24 h), cells were exposed to the medium ( t = 0 h), and viability was assessed after 24 h. All materials and material combinations showed no cytotoxicity, , i.e.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Thus, we tested the utilized materials for cytotoxicity, as well as for biocompatibility to overgrowing cells. According to the ISO 10993 standard, ≥30% reduction in cell viability after exposure to a device is considered cytotoxic. , First, we ran an indirect cytotoxicity test using the individual materials and combinations of materials. Specifically, the materials were incubated for 24 h in the culture medium ( t = 24 h), cells were exposed to the medium ( t = 0 h), and viability was assessed after 24 h. All materials and material combinations showed no cytotoxicity, , i.e.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Recently, Hsieh et al prepared a hydrogel MN patch that can extract sufficient ISF rapidly, and then the ISF in the needles can be recovered into a moist cellulose paper through spontaneous diffusion. 88 The paper can be functionalized with a plasmonic array or enzymatic colorimetric reagents, enabling a desired detection capacity. The authors functionalized the cellulose paper with Au nanoparticles (AuNPs) to serve as an ultrasensitive, label-free SERS sensing platform.…”
Section: Integrated Mn Sensing Systemsmentioning
confidence: 99%
“…Besides, the authors also demonstrated the use of paper for colorimetric analysis. 88 They pre-loaded the cellulose paper with specific oxidases and dye reagents, according to the nature of the target biomolecule. Then, the color readout would be in response to the target concentration, allowing rapid determination by the naked eye.…”
Section: Integrated Mn Sensing Systemsmentioning
confidence: 99%
See 2 more Smart Citations